Admission Heart Rate Variability Is Associated With Poststroke Depression in Patients With Acute Mild-Moderate Ischemic Stroke - He, Lanying; Wang, Jian; Zhang, Lijuan; Wang, Feng; Dong, Weiwei; Yang, Hao (Frontiers in Psychiatry, 2020)
Background: Stroke has been shown to cause cardiac autonomic dysfunction. Depression is common complication after acute ischemic stroke (AIS). The purpose of this study was to investigate whether decreased heart rate variability (HRV) was related to poststroke depression (PSD) in patients with mild-moderate AIS. Methods: In this study, we assessed autonomic function of ischemic stroke patients within 72 h from symptom onset by fractal dimension (FD). 503 patients (mean age 65.93±10.19) with mild-moderate AIS underwent FD test after admission. Depressive symptoms were assessed using 17-item Hamilton Depression Rating Scale (HDRS) at baseline (within 7 days) and 3 months. Depression were defined if HDRS >6 points. According to the data of FD, we investigated association with early onset PSD status and 3-month PSD. Results: 59.24% (293/503) of patients had early onset PSD status at baseline, and 38.66% (184/476) of patients had PSD at 3 months. ROC curve analysis shown that the optimal cut point of FD for early onset PSD status and 3-month PSD were FD≤1.27 and FD≤1.19, respectively. In fully adjusted models, higher NIHSS [adjusted odd ratios(OR), 1.15; 95% confidence interval (CI), 1.05–1.27; P=0.005], younger age (adjusted OR, 1.18; 95%CI, 1.01–1.13; P=0.046), and FD≤1.27 (adjusted OR, 3.31; 95%CI, 2.23–4.92; P<0.001) were associated with increased risk of early onset PSD status. Higher NIHSS (adjusted OR, 1.21; 95%CI, 1.09–1.43; P<0.001) and FD≤1.19 (adjusted OR, 2.68; 95%CI, 1.79–4.03; P=0.000) were associated with increased risk of 3-month PSD. Conclusions: PSD is common after mild-moderate AIS and is highly correlated with decreased HRV, FD could serve as an objective tool to help in prediction of PSD.